The Electromagnetic Counterpart of the Binary Neutron Star Merger LIGO/Virgo GW170817. III. Optical and UV Spectra of a Blue Kilonova from Fast Polar Ejecta - Nicholl, M. (2017)
We present optical and ultraviolet spectra of the first electromagnetic counterpart to a gravitational-wave (GW) source, the binary neutron star merger GW170817. Spectra were obtained nightly between 1.5 and 9.5 days post-merger, using the Southern Astrophysical Research and Magellan telescopes; the UV spectrum was obtained with the Hubble Space Telescope at 5.5 days. Our data reveal a rapidly fading blue component (T ≈ 5500 K at 1.5 days) that quickly reddens; spectra later than ≳4.5 days peak beyond the optical regime. The spectra are mostly featureless, although we identify a possible weak emission line at ∼7900 Å; at t ≲ 4.5 days. The colors, rapid evolution, and featureless spectrum are consistent with a "blue" kilonova from polar ejecta comprised mainly of light r-process nuclei with atomic mass number A ≲ 140. This indicates a sightline within θobs ≲ 45° of the orbital axis. Comparison to models suggests ∼0.03 M o of blue ejecta, with a velocity of . The required lanthanide fraction is ∼10-4, but this drops to <10-5in the outermost ejecta. The large velocities point to a dynamical origin, rather than a disk wind, for this blue component, suggesting that both binary constituents are neutron stars (as opposed to a binary consisting of a neutron star and a black hole). For dynamical ejecta, the high mass favors a small neutron star radius of ≲12 km. This mass also supports the idea that neutron star mergers are a major contributor to r-process nucleosynthesis.